An Effectively Modified Firefly Algorithm for Economic Load Dispatch Problem - Nguyen Trung Thang; Nguyen Duy Phuong; Pham Van Thanh; Chiem Trong Hien (Universitas Ahmad Dahlan, 2018)
This paper proposes an effectively modified firefly algorithm (EMFA) for searching optimal solution of economic load dispatch (ELD) problem. The proposed method is developed by improving the procedure of new solution generation of conventional firefly algorithm (FA). The performance of EMFA is compared to FA variants and other existing methods by testing on four different systems with different types of objective function and constraints. The comparison indicates that the proposed method can reach better optimal solutions than other FA variants and most other existing methods with lower population and lower maximum iteration. As a result, it can lead to a conclusion that the proposed method is potential for ELD problem.